Process for modifying silica in liquid phase

By reacting hydrophilic silica with liquid polyorganosiloxane in an organic solvent, the modified silica is formed, which solves the problem of long-term mixing time in the prior art, and achieves a good polymer matrix Improved shear thinning performance and production efficiency.

CN119497739APending Publication Date: 2025-02-21WACKER CHEMIE AG
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202280097600.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-06-29
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The prior art when the modified silica is incorporated into a polymer matrix, the mixing time is longer, affecting the maximum yield and application efficiency.

Method used

By reacting hydrophilic silica with liquid polyorganosiloxane in a suspension in an organic solvent, a chain silicone structure is formed, and the modified silica is carried out at medium temperature to ensure the silicone chain Good bond with silica surface.

Benefits of technology

Modified silica exhibits good shear thinning performance in polymer matrix, with significantly reduced mixing time, improving production efficiency and product performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005214033900000061
    Figure BDA0005214033900000061
Patent Text Reader

Abstract

The invention relates to a method for surface modification of hydrophilic silica having a specific surface area of 10 to 1000 m2 / g (measured by the BET method according to DIN EN ISO 9277 / DIN 66132), in which a suspension of silica in an organic solvent is reacted with a liquid polyorganosiloxane consisting of two units of general formula R1R2R3SiO1 / 2 (M) and 0 to 20 units of general formula R4R5Si (O1 / 2) 2 (D), wherein each of R1, R2, R3, R4 and R5 is a hydroxyl group or a monovalent hydrocarbon group having 1 to 24 carbon atoms, and wherein at least one group R1, R2, R3, R4, R5 and at most 20 mol% based on all groups R1, R2, R3, R4, R5 is a hydroxyl group.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to a method for surface modification of hydrophilic silicon dioxide in a suspension of silicon dioxide in an organic solvent by using liquid polyorganosiloxane.

[0002] Hydrophobic surface-modified silica modified with polydimethylsiloxane (PDMS) or chloromethylsilane is used as a thickener and thixotropic agent in composites, coatings and adhesives, especially in vinyl ester systems, epoxy systems and polyurethane systems.

[0003] To obtain surface-modified silica, for example according to WO2008077814 or EP2824148, hydrophilic silica is fluidized in the gas phase and functionalized with a PDMS-containing plasticizer. In order to obtain particularly good bonding of the PDMS chains to the silica surface, a subsequent heat treatment at 150 to 350° C. is particularly important. This results in a very low volatile content of less than 0.6% (2 hours at 105° C.). However, this material has the disadvantage of a very high incorporation time. Since the incorporation of silica into a polymer matrix is ​​a cycle time-determining step in many commercial applications, the maximum yield is closely related to the incorporation time.

[0004] The present invention provides a surface modification method of hydrophilic silicon dioxide, wherein the specific surface area of ​​the hydrophilic silicon dioxide is 10 to 1000 m 2 / g (measured by the BET method according to DIN EN ISO 9277 / DIN 66132), wherein a suspension of silicon dioxide in an organic solvent is mixed with two molecules of the general formula R 1 R 2 R 3 SiO 1 / 2 (M) units and 0-20 general formula R 4 R 5 Si(O 1 / 2 )2(D) units, wherein R 1 , R 2 , R 3 , R 4 and R 5 are each a hydroxyl group or a monovalent hydrocarbon group having 1 to 24 carbon atoms, wherein at least one group R 1 , R 2 , R 3 , R 4 , R 5 and based on all groups R 1 , R 2 , R 3 , R 4 , R 5 At most 20 mol % are hydroxyl groups.

[0005] Compared with conventionally modified silicas, silicas modified in this way have consistently good shear thinning in the polymer matrix and the incorporation time is significantly reduced.

[0006] Silica modification is carried out in the liquid phase at moderate temperatures.

[0007] The surface of the silicon dioxide modified by this method has a chain siloxane structure with a chain length distribution that is as uniform as possible. These siloxane chains are preferably permanently fixed on the silicon dioxide surface as completely as possible. In addition, the siloxane chains are preferably chemically bonded to the surface of the silicon dioxide via a separate attachment site.

[0008] The silicon dioxide used may be, for example, precipitated silicon dioxide or fumed silicon dioxide.

[0009] Particularly preferred are fumed silicas prepared from organosilicon compounds in a flame reaction, for example from silicon tetrachloride or methyltrichlorosilane, or hydrogentrichlorosilane or hydrogenmethyldichlorosilane, or other methylchlorosilanes or alkylchlorosilanes, including in a mixture with hydrocarbons, or in any desired volatile or sprayable mixtures of organosilicon compounds and hydrocarbons as mentioned, for example in an oxyhydrogen flame or a carbon monoxide-oxygen flame. The silica can be prepared with or without additional addition of water, for example in a purification step; preferably no water is added.

[0010] The silicon dioxide used preferably has a molecular weight of 40 to 400 m 2 / g, particularly preferably 150 to 270 m 2 Specific surface area of ​​100 g (measured by the BET method according to DIN EN ISO 9277 / DIN 66132).

[0011] The bulk density of the silicon dioxide used (determined in accordance with DIN EN ISO 787-11) can be from 10 to 200 g / l, preferably from 20 to 100 g / l and particularly preferably from 20 to 60 g / l.

[0012] The degree of modification obtained by this method can be analyzed by measuring the residual silanol content. The residual silanol content of the modified silica is preferably 30 to 90 mol%, particularly preferably 45 to 85 mol%, and especially preferably 55 to 75 mol%. For example, a suitable method for measuring the residual silanol content after modification by acid-base titration is described in GW Ears et al. Analytical Chemistry 1956, 28, 1981ff.

[0013] The carbon content achieved by this process is preferably from 1% to 15% by weight, particularly preferably from 2% to 10% by weight, particularly preferably from 3% to 8% by weight.

[0014] The groups introduced by the modification are firmly bound to the surface of the silicon dioxide. Firm bonding represents a good chemical bond and is quantified according to the invention by the fraction of the modified silicon dioxide that can be extracted with a solvent, which fraction is preferably at most 10 wt %. The extractable fraction is particularly preferably at most 6 wt %, in particular at most 4 wt %, particularly preferably at most 2 wt %. A suitable method for evaluating the bond strength of the modification is the quantitative determination of extractable polyorganosiloxanes, i.e. polyorganosiloxanes that are not chemically bonded to the surface of the modified silicon dioxide.

[0015] Methyl isobutyl ketone MIBK is preferably used for determining extractable polyorganosiloxanes.

[0016] Monovalent hydrocarbon group R 1 To R 5 may be identical or different and are selected from saturated, monounsaturated or polyunsaturated, unbranched or branched hydrocarbon radicals, which optionally have heteroatoms and / or functional groups.

[0017] Preferably, the hydrocarbon radical is an alkyl, alkenyl and aryl radical, for example methyl, ethyl, propyl, such as n-propyl or isopropyl, butyl, such as n-butyl, isobutyl or tert-butyl, hexyl, such as n-hexyl or isohexyl, octyl, such as n-octyl or isooctyl, dodecyl, tetradecyl, hexadecyl, octadecyl, vinyl, allyl, phenyl, o-tolyl, m-tolyl, p-tolyl, xylyl, mesityl or naphthyl.

[0018] The alkyl or aryl group may also have other heteroatoms or functional groups. Here, the preferred general formula is R=(CH2) n Y is a monovalent organic radical wherein n=1-24 and Y=vinyl, acrylate, methacrylate, glycidyloxy, —SH, —OH, a primary amine group (—NH2), a secondary amine group (—NHR), such as N-monomethyl, N-monoethyl, N-monopropyl, N-monobutyl, N-cyclohexyl or anilino, a tertiary amine group (—NR2) such as N,N-dimethyl, N,N-diethyl, N,N-dipropyl, N,N-dibutyl, N,N-methylethyl, N,N-methylpropyl, N,N-ethylpropyl, N,N-methylphenyl, morpholinyl, pyrrolyl, indolyl, pyrazolyl, imidazolyl or piperidinyl, a quaternary amine group such as N,N,N-trimethylammonium, N,N,N-triethylammonium or N,N,N-tripropylammonium, a phosphonate, —P(O)(OR 6 )2(R 7isocyanate and protected isocyanate (-N(H)C(O)G, wherein the protecting group G is eliminated as HG under thermal stress, wherein HG = methyl 2-hydroxybenzoate, 2-hydroxypyridine, 1-hydroxymethyl-1,2,4-triazole, N,N-diethylhydroxylamine, 2-butanone oxime, dimethyl malonate, ethyl acetoacetate, diisopropylamine, tert-butylbenzylamine, tert-butylmethylamine, tert-butylisopropylamine, 2-isopropylimidazole, 3,5-dimethylpyrazole or ε-caprolactam) or dihydro-3-yl-2,5-furandione.

[0019] In addition, there may be a general formula R 11 Si(O 1 / 2 )3 other organosilicon groups, wherein the substituent R 11 is selected from the hydrocarbon groups specified for R above.

[0020] Monovalent hydrocarbon group R 1 To R 5 It is preferably selected from the group consisting of methyl, ethyl, propyl, butyl and phenyl.

[0021] The polyorganosiloxanes used in the process preferably have 0 to 15 units, particularly preferably 1 to 10 units and in particular 2 to 10 units of the general formula R 4 R 5 Si(O 1 / 2 )2(D).

[0022] The polyorganosiloxane used in the process is preferably liquid at 0 to 60° C., particularly preferably at 10 to 50° C., especially preferably at 15 to 30° C., at 0.10 MPa (abs.).

[0023] The average viscosity of the polyorganosiloxane used in the process at 20° C. is preferably from 5 to 200 mPa·s, particularly preferably from 10 to 100 mPa·s, in particular from 20 to 60 mPa·s.

[0024] The polyorganosiloxanes can be used in any desired amounts. The amounts used are preferably 5% to 50% by weight, particularly preferably 20% to 40% by weight and in particular 15% to 25% by weight, in each case based on the unmodified hydrophilic silica.

[0025] In one embodiment of the present invention, polyorganosiloxane is used together with an additive auxiliary.

[0026] The organic solvent used for preparing the silica suspension is preferably an aprotic solvent, preferably with a boiling point of up to 120° C., in particular up to 100° C., in each case at 0.10 MPa (abs.), for example a ketone such as acetone, methyl ethyl ketone, an ether such as diethyl ether, dioxane, a hydrocarbon such as pentane, hexane, an aromatic compound such as toluene or another solvent such as hexamethyldisiloxane. Mixtures can also be used.

[0027] Optionally, a protic solvent can be additionally added to the process. If a molecule has a functional group from which a hydrogen atom can be eliminated (dissociated) as a proton, the solvent is called a protic solvent. Due to the high polarity of the OH bond, it can be split relatively easily by eliminating a positively charged hydrogen atom (proton).

[0028] The most important protic solvent is water, which dissociates (in simple terms) into protons and hydroxide ions. Examples of other protic solvents include alcohols and carboxylic acids. According to the invention, liquid or evaporable alcohols such as isopropanol, ethanol or methanol or water can be added as protic solvents, for example. Mixtures of the above-mentioned protic solvents can also be added. Based on the silicon dioxide, preferably 1% to 50% by weight of protic solvents are added, particularly preferably 5% to 25% by weight. Particularly preferably, water is added as protic solvent.

[0029] In the surface modification of hydrophilic silica, substances that shorten the required reaction time and / or can reduce the process temperature can also be used. These catalytic or stoichiometrically effective substances are referred to as auxiliary agents hereinafter. They preferably include acidic or alkaline reaction substances. They can be selected, for example, from Lewis acids, which include, for example, trivalent aluminum and boron compounds. It is also preferred to use Bronsted acids, such as hydrogen halides or organic acids. Hydrogen chloride or acetic acid are particularly preferred here. In another embodiment, basic reaction compounds, such as hydroxides of alkali metals and alkaline earth metals, and salts thereof derived from corresponding alcohols or carboxylic acids are used as auxiliary agents. In addition, they can be selected from nitrogen-containing compounds such as ammonia or organically substituted primary, secondary or tertiary amines. The monovalent organic substituents of the alcohols, carboxylic acids and amines include saturated and unsaturated, branched and non-branched hydrocarbon groups, which can also have other heteroatoms or functional groups. The auxiliary agent can be added in pure form or as a solution in an inert or reactive solvent. Preference is given to using aqueous sodium hydroxide or potassium hydroxide solution, aqueous ammonia solution, isopropylamine, n-butylamine, isobutylamine, tert-butylamine, cyclohexylamine, triethylamine, morpholine, piperidine or pyridine.

[0030] In a preferred embodiment, the amount of the auxiliary agent used is 0.1% to 10% by weight, based on the unmodified silicon dioxide. Preference is given to using 0.2% to 5% by weight. Particular preference is given to using 0.5% to 1.5% by weight of auxiliary agent, based on the unmodified silicon dioxide.

[0031] The temperature in the surface modification of the hydrophilic silica is preferably 20 to 140° C. at 0.10 MPa (abs.), particularly preferably 30 to 120° C., particularly preferably 40 to 100° C.

[0032] The removal of the solvent, excess polyorganosiloxane and by-products may preferably be performed by a dryer or spray drying.

[0033] Optionally, the drying step may be followed by a subsequent reaction step to complete the reaction.

[0034] The subsequent reaction is preferably carried out at a temperature of 20 to 300°C, preferably 20 to 200°C, particularly preferably 40 to 180°C.

[0035] Furthermore, after the drying step, a process for deagglomeration of the modified silica may be used, such as a pin mill, a hammer mill, a countercurrent mill, an impact mill, or an apparatus for grinding and classification.

[0036] Analytical methods:

[0037] Determination of carbon content (%C)

[0038] The elemental analysis of carbon was carried out according to DIN ISO 10694 using a CS-530 elemental analyzer from Eltra GmbH (D-41469 Neuss).

[0039] Determination of residual silanol content of unmodified silica

[0040] The residual silanol content was determined by acid-base titration of silica suspended in a 1:1 mixture of water and methanol, similar to the method of GW Ears et al. Analytical Chemistry 1956, 28, 1981ff. The titration was performed in the region above the isoelectric point of silica and below the pH range in which silica dissolves.

[0041] Therefore, the residual silanol content (%) can be calculated according to the following formula:

[0042] SiOH=SiOH(silyl) / SiOH(phil)*100%

[0043] in

[0044] SiOH(phil): titration volume of untreated silica

[0045] SiOH(Silyl): Titration volume for silylated silica

[0046] Determination of the extractable fraction (i.e. the fraction from which polyorganosiloxane can be extracted)

[0047] In a screw-top PE container, 2.5 g of the silica used for the study were stirred into 47.5 g of MIBK using a spatula and the container was then closed. After a 30-minute standing time in an ice bath, the mixture was treated in an ice-cooled ultrasound bath (Sonorex Digitec DT 156, BANDELIN electronic GmbH & Co. KG, D-12207 Berlin) for 30 minutes and then passed through a PTFE membrane filter (pore size: 0.2 μm, diameter: 47 mm, Sartorius AG, ) was filtered under pressure (5 bar nitrogen) to obtain a clear filtrate. 10.00 ml of the filtrate was accurately taken out as an analyte, and the silicon content was determined by atomic absorption spectroscopy (Atom Absorption Spectrometer 2100, Perkin Elmer Waltham, MA, USA) and weighed.

[0048] The weight % of extractable components can be calculated as a first approximation as follows:

[0049]

[0050] in

[0051] m(MIBK): initial weight of MIBK (=47.50 g)

[0052] V(analyte): volume of analyte (=10.00 mL)

[0053] m(silicon dioxide): initial weight of surface-modified silicon dioxide (=2.50 g)

[0054] m(Si): molar mass of silicon (=28.09 g / mol)

[0055] c(analyte): silicon content of the analyte (mg / L)

[0056] m(analyte): final weight of analyte (g)

[0057] M(R4R5SiO2 / 2): molecular weight of the D group R4R5SiO2 / 2 (g / mol)

[0058] Determination of viscosity of polyorganosiloxane

[0059] The determination was carried out in accordance with DIN 53019 at 20° C. and 0.10 MPa (abs.). Example

[0060] In the following examples, unless otherwise specified, all numbers for amounts and percentages are based on weight, all pressures are 0.10 MPa (abs.), and all temperatures are 20° C. in each case.

[0061] Example 1: Preparation of highly hydrophobic silica in a 2 L glass reactor followed by grinding

[0062] First, under argon protection, 1140 g of solvent hexamethyldisiloxane was loaded into a round 2L glass reactor equipped with a precision glass stirrer. The reactor was covered with a glass cover having a total of four ground glass necks, and a reflux condenser with a bubble counter and a thermometer immersed in the reactor were provided. Under argon protection, a total of 150 g of silica HDK N20 (initial surface area of ​​200 m2) was added through a grounded metal funnel using a metal shovel. 2 / g of silica, commercially available from WackerChemie AG), and a suspension was prepared under vigorous stirring with a precision glass stirrer. Finally, 4g of an aqueous ammonia solution (concentration: 5 mol / L) and 21g of a plasticizer X345 (a mixture of short-chain α-hydroxypolydimethylsiloxanes with an average viscosity of 35 to 50 mPa·s) were added to the suspension.

[0063] Under vigorous stirring, the 2L glass reactor was immersed as much as possible in an oil bath heated to 120°C using a magnetic stirrer (Heidolph Instruments Mr Hei-Tec magnetic stirrer). The suspension was heated to 93°C and boiled under reflux for 2 hours. Once the mixture cooled to room temperature, the solvent and any unreacted reactants were removed in a rotary evaporator (Heidolph Instruments) with a vacuum pump and a cold trap, with an oil bath temperature of 130°C.

[0064] The dry silica thus obtained was broken down in a fine grinding apparatus (Sugino Dry Burst DB-100S CE, a countercurrent dry mill).

[0065] The silica according to the invention has a carbon content of 4.8 wt %. The rheological properties were tested as follows: The modified silica was dispersed in epoxy resin and after storage for one day, the rheological properties were tested at 0.1 s -1 and 10s -1 The viscosity of the mixture was measured at a shear rate of 1.5 Å. The thixotropic index was obtained by dividing the viscosity at a low shear rate by the viscosity at a high shear rate. The thixotropic index and mixing time of two epoxy resin systems were determined:

[0066] Epoxy resin system 1:

[0067] A mixture of 8 wt % modified silica and 92 wt % epoxy resin (Epikote™ Resin 828 from Hexion, a commercial epoxy resin based on bisphenol A and epichlorohydrin).

[0068] The thixotropic index of the silica modified according to the invention was 38. The mixing-in time of this silica according to the invention was 160 seconds.

[0069] For comparison, conventional silicon dioxide X which was not modified according to the invention and which consisted of HDK N20 modified with plasticizer X345 in the gas phase and had a carbon content of 4.8% by weight was used.

[0070] The comparable thixotropy index of silica X is 34. The mixing-in time for this silica not according to the invention is 360 seconds.

[0071] Epoxy Resin System 2:

[0072] A mixture of 8 wt% modified silica in epoxy resin (Epikote™ Resin 828 from Hexion, a commercial epoxy resin based on bisphenol A and epichlorohydrin) and 4 wt% HDK N20 in an amine curing agent (Epikure™ Curing Agent MGSO RIMH-137 from Hexion) with a mixing ratio of 79 wt% epoxy resin and 21 wt% amine curing agent.

[0073] The two epoxy resin systems were identical, but in the case of the second system the amine curing agent was added shortly before the measurement. Thus, for both epoxy resin systems, the same mixing-in time was obtained in each case.

[0074] The thixotropic index of the silica modified according to the invention is 54.

[0075] Example 2: Preparation of highly hydrophobic silica in a 2L three-necked flask followed by heat treatment

[0076] Under argon protection, initially 855g solvent hexamethyldisiloxane is joined in the 2L three-necked glass flask equipped with precision glass stirrer.Flask is equipped with reflux condenser and thermometer with bubble counter.Under argon protection, use metal shovel to add silicon dioxide N20 totaling 112g by grounded metal funnel, and prepare suspension under vigorous stirring with precision glass stirrer.Finally, in suspension, add 3g ammonia solution (concentration: 5mol / L) and 16g plasticizer X345.

[0077] Under vigorous stirring, a three-necked flask was provided with a heating mantle (Carlroth Heating mantle). The suspension was heated to 50°C and kept at this temperature for 2 hours with vigorous stirring. Once the mixture had cooled to room temperature, the solvent and any unreacted reactants were removed in a rotary evaporator (Heidolph Instruments) with a vacuum pump and cold trap, with an oil bath temperature of 130°C.

[0078] The silicon dioxide thus obtained was then heat treated in a nitrogen-purged drying oven at 200° C. for 1 hour. The final silicon dioxide according to the invention had a carbon content of 4.8% by weight.

[0079] Epoxy resin system 1:

[0080] The thixotropic index of the silica modified according to the invention was 36. The mixing-in time of this silica according to the invention was 9 seconds.

[0081] The comparable thixotropic index of silica X is 34. The mixing-in time for this silica not according to the invention is 186 seconds.

[0082] Epoxy Resin System 2:

[0083] The thixotropic index of the silica modified according to the invention is 56.

[0084] The comparable thixotropic index of Silica X is 60.

Claims

1. A method for surface modification of hydrophilic silica, wherein the hydrophilic silica has a specific surface area of ​​10 to 1000 m 2 / g (measured by the BET method according to DIN EN ISO 9277 / DIN 66132), wherein a suspension of the silicon dioxide in an organic solvent is reacted with a liquid polyorganosiloxane consisting of two molecules of the general formula R 1 R 2 R 3 SiO 1 / 2 (M) units and 0-20 general formula R 4 R 5 Si(O 1 / 2 )2(D) units, where R 1 , R 2 , R 3 , R 4 and R 5 are each a hydroxyl group or a monovalent hydrocarbon group having 1 to 24 carbon atoms, wherein at least one group R 1 , R 2 , R 3 , R 4 , R 5 and based on all groups R 1 , R 2 , R 3 , R 4 , R 5 At most 20 mol % are hydroxyl groups.

2. The method of claim 1, wherein fumed silica is used.

3. The process as claimed in one or more of the preceding claims, wherein the carbon content obtained by the process is from 1% to 15% by weight.

4. The process as claimed in one or more of the preceding claims, wherein the monovalent hydrocarbon radical R 1 To R 5 Selected from methyl, ethyl, propyl, butyl and phenyl.

5. The process as claimed in one or more of the preceding claims, wherein the polyorganosiloxane is liquid at 0.10 MPa (abs.) in the range from 0 to 60°C.

6. The process as claimed in one or more of the preceding claims, wherein the organic solvent used for preparing the suspension of silicon dioxide is an aprotic solvent.

7. The process as claimed in claim 6, wherein a protic solvent is additionally added.

Citation Information

Patent Citations

  • Highly disperse silica having a high positive surface charge

    EP2824148A1